The Continuous Classical Optimal Control governing by Triple Linear Parabolic Boundary Value Problem - Al-Hawasy, Jamil Amir Ali; Jaber, Mohammed A. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
This paper deals with the continuous classical optimal control problem for triple partial differential equations of parabolic type with initial and boundary conditions; the Galerkin method is used to prove the existence and uniqueness theorem of the state vector solution for given continuous classical control vector. The proof of the existence theorem of a continuous classical optimal control vector associated with the triple linear partial differential equations of parabolic type is given. The derivation of the Fréchet derivative for the cost function is obtained. At the end, the theorem of the necessary conditions for optimality of this problem is stated and is proved.